2018
DOI: 10.1101/306134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Transcriptomics of Pancreatic Cancer Precursors Demonstrates Epithelial and Microenvironmental Heterogeneity as an Early Event in Neoplastic Progression

Abstract: Key Words: single-cell RNA sequencing, pancreatic cancer, intraductal papillary mucinous neoplasm, transcriptomic heterogeneity, precancer atlas Word Count: 3794All rights reserved. No reuse allowed without permission.(which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/306134 doi: bioRxiv preprint first posted online Apr. 26, 2018; Abstract Background: Early detection of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…The function of Ly-6C remains widely unknown, yet, it is mainly associated with the immune system, and inflammatory events (6365). We identified Ly-6C as characteristic marker for CAFs, which is in line with current literature (6668). Ly-6C has been introduced as cell surface marker characteristic for a subpopulation of activated (cancer-associated) fibroblasts, termed inflammatory CAFs [iCAFs; (6668)].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The function of Ly-6C remains widely unknown, yet, it is mainly associated with the immune system, and inflammatory events (6365). We identified Ly-6C as characteristic marker for CAFs, which is in line with current literature (6668). Ly-6C has been introduced as cell surface marker characteristic for a subpopulation of activated (cancer-associated) fibroblasts, termed inflammatory CAFs [iCAFs; (6668)].…”
Section: Discussionsupporting
confidence: 90%
“…We identified Ly-6C as characteristic marker for CAFs, which is in line with current literature (6668). Ly-6C has been introduced as cell surface marker characteristic for a subpopulation of activated (cancer-associated) fibroblasts, termed inflammatory CAFs [iCAFs; (6668)]. However, our data suggested Ly-6C to be a general fibroblast marker upregulated upon activation or proliferation and generally overexpressed in CAFs.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that CAFs are a major source of TGFb-induced IL-6 expression. Several recent studies including ours demonstrate the existence of fibroblast heterogeneity within PDA (Ohlund et al, 2017;Bernard et al, 2019;Elyada et al, 2019;Hosein et al, 2019). Two major populations of CAFs have been identified, one is characterized by an inflammatory feature, while the other has been known as myofibroblast.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, several studies, including ours, suggest the existence of two different subtypes of CAFs in PDA (Ohlund et al, 2017;Bernard et al, 2019;Elyada et al, 2019;Hosein et al, 2019). Of the two CAF populations, one appears to be inflammatory, characterized by PDGFRa expression and the secretion of a variety of inflammatory chemokines.…”
mentioning
confidence: 70%
“…Myeloid cell populations are highly heterogenous (30,31). While many myeloid cell populations can stimulate immune evasion via a wide range of immunosuppressive mechanisms, some myeloid cells have anti-tumor properties (32).…”
Section: Discussionmentioning
confidence: 99%